PERAN BHABINKAMTIBMAS SERTA MASYARAKAT DALAM UPAYA PENCEGAHAN GANGGUAN KEAMANAN DAN PENYELESAIAN SENGKETA DI KABUPATEN LABUHANBATU - Wahyu Simon Tampubolon (Universitas Labuhanbatu, 2020)
The Indonesian National Police is directly responsible under the President. The police carry out police duties throughout Indonesia. The police are one of the foremost persons of society, the role of the police at this time is as a guardian of security and order as well as law enforcement officers in society related to criminal law, the police are able to carry out their duties professionally, where their birth originates from the community, according to their needs and desires they. This is done in order to create a situation and conditions that are safe, orderly, serene, and peaceful in social life, which then develops in accordance with developments and changes in state conditions. The National Police, which started from the public side, is now on the side of the state, which has a role to face and control the community itself. Law Number 2 of 2002 concerning the State Police of the Republic of Indonesia, the duties, authorities and rights of the police, in which Article 2 the function of the National Police is to maintain security and public order (kamtibmas).In accordance with the philosophical foundation of the Unitary State of the Republic of Indonesia is Pancasila which is the basis of our country, especially the fourth principle